Ethical Assumptions of Sustainable Development Education - Tyburski, Włodzimierz (Problemy Ekorozwoju, 2007)
The article is trying to present main ethical ideas supporting the education for sustainable development. The interest is focused on the following topics: presentation of general assumptions of sustainable development education, philosophical basis of the idea of sustainable development, values of life, health, justice, responsibility, moderateness and solidarity, the role and importance of developmental ethics for the idea of sustainable development, the cognitive, volitive and behavioral levels of action in the scope of developmental education being an element of education for sustainable development.